All-Inside Repair of a Radial Lateral Meniscal Root Tear With an Anterior Cruciate Ligament Injury - Amar S. Vadhera BS; Derrick M. Knapik MD; Suhas P. Dasari MD; Harsh Singh BA; Nikhil N. Verma MD; Jorge Chahla MD, PhD (SAGE Publishing, 2022)
Background: Root tears are functionally compromising injuries that require an anatomic repair for functional restoration of native joint mechanics. Posterior root tears of the lateral meniscus are commonly associated with anterior cruciate ligament (ACL) ruptures as lateral root tears contribute to anterolateral rotational instability. Two-tunnel transtibial root repair allows for root repair with superior pullout strength and can be combined with ACL reconstruction to treat this injury pattern. Indications: Two-tunnel transtibial root repair is indicated in active patients with meniscal root tears that have low-grade chondromalacia (grade II or less). It is contraindicated in patients with advanced degenerative changes (grade III-IV), severe mal-alignment, and extrusion related to advanced degenerative changes; those who cannot complete postoperative rehabilitation; and patients with significant medical comorbidities. Technique Description: After repairing a vertical horn tear of the posterior medial meniscus, a vertical tear of the posterior root of the lateral meniscus was observed. Following preparation of the anatomic footprint, 2 transtibial tunnels were drilled and sutures were passed and secured using a surgical button over the anterior tibial cortex. Horizontal repair of the tear was then performed using 2 all-inside devices. Subsequently, an ACL reconstruction was performed. Results: At 11 months postoperative, the patient has continued to progress as expected. She was able to ambulate without pain, had a symmetric and balanced gait, and was able to return to running. Discussion/Conclusion: Lateral meniscal root repairs using 2 transtibial tunnels and concomitant ACL reconstruction have yielded good and reliable clinical outcomes with low failure rates and low rates of revision surgery.